Heterogeneous Effects of Credit Constraints on SMEs' Employment: Evidence from the Great Recession - David Cornille; Francois Rycx; Ilan Tojerow (Institute of Labor Economics (IZA), 2018)
This paper takes advantage of access to detailed matched bank-firm data to investigate whether and how employment decisions of SMEs have been affected by credit constraints in the wake of the Great Recession. Variability in banks' financial health following the 2008 crisis is used as an exogenous determinant of firms' access to credit. Findings, relative to the Belgian economy, clearly highlight that credit matters. They show that SMEs borrowing money from pre-crisis financially less healthy banks were significantly more likely to be affected by a credit constraint and, in turn, to adjust their labour input downwards than pre-crisis clients of more healthy banks. These results are robust across types of loan applications that were denied credit, i.e. applications to finance working capital, debt or new investments. Yet, estimates also show that credit constraints have been essentially detrimental for employment among SMEs experiencing a negative demand shock or facing strong product market competition. In terms of human resources management, credit constraints are not only found to foster employment adjustment at the extensive margin but also to increase the use of temporary layoff allowances for economic reasons. This outcome supports the hypothesis that short-time compensation programmes contribute to save jobs during recessions.
Keywords: C35; C36; D22; G01; G21; J21; J23; 330; SMEs; banks' financial health; credit constraints; employment; short-time compensation programmes; Great Recession; matched bank-firm data